2017
DOI: 10.26434/chemrxiv.5393947
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the reliability of volume-based thermodynamics for inorganic-organic salts and coordination compounds with uncharged ligands

Abstract: In the present work, the reliability of the volume-based thermodynamics (VBT) methods in the calculation of lattice energies is investigated by applying the "traditional" Kapustinskii equation [8]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Initially, the VBT method was developed with ionic salts, complex ionic systems, and inorganic structures. Recent studies were conducted in the field of actinides, , organic ligands, and uncharged ligands, broadening the application of this method. However, the lack of experimental data on formation energetics can sometimes make it challenging to validate the VBT findings.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the VBT method was developed with ionic salts, complex ionic systems, and inorganic structures. Recent studies were conducted in the field of actinides, , organic ligands, and uncharged ligands, broadening the application of this method. However, the lack of experimental data on formation energetics can sometimes make it challenging to validate the VBT findings.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies were conducted in the field of actinides, 28,38 organic ligands, 39 and uncharged ligands. 40 Thermodynamic stability in the form of Gibbs energy is a valuable indicator into the likelihood of compound decomposition, thus providing insight into possible uranium-based precursors that could be converted to a metallic form. 30 We have previously shown that the stability of complex compounds containing uranium can be predicted using volume-based thermodynamic (VBT) methods 28,38 while conventional thermodynamic modeling techniques, such as density functional theory (DFT) or the CALPHAD method (CALculation of PHAse Diagrams), fall short in treating these complicated structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%